2017
DOI: 10.1038/srep41363
|View full text |Cite
|
Sign up to set email alerts
|

Cold-inducible RNA-binding protein (CIRP) causes sepsis-associated acute lung injury via induction of endoplasmic reticulum stress

Abstract: Cold-inducible RNA-binding protein (CIRP), released into the circulation during sepsis, causes lung injury via an as yet unknown mechanism. Since endoplasmic reticulum (ER) stress is associated with acute lung injury (ALI), we hypothesized that CIRP causes ALI via induction of ER stress. To test this hypothesis, we studied the lungs of wild-type (WT) and CIRP knockout (KO) mice at 20 h after induction of sepsis by cecal ligation and puncture (CLP). WT mice had significantly more severe ALI than CIRP KO mice. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 81 publications
(134 reference statements)
1
73
0
Order By: Relevance
“…CIRP also causes EC dysfunction by increasing inflammasome-mediated pyroptosis in sepsis [8, 9, 11]. It has recently been shown that CIRP induces lung endoplasmic reticulum (ER) stress and its associated downstream responses to promote sepsis-associated ALI [10]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CIRP also causes EC dysfunction by increasing inflammasome-mediated pyroptosis in sepsis [8, 9, 11]. It has recently been shown that CIRP induces lung endoplasmic reticulum (ER) stress and its associated downstream responses to promote sepsis-associated ALI [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The protective and harmful effects of neutrophils depend on the stages of sepsis, as at the onset of sepsis neutrophils are important in attenuating bacteremia, whereas at the late onset of sepsis prolonged and excessive infiltration of neutrophils often cause organ dysfunction [36]. An indirect role of CIRP on neutrophils to cause ARDS was shown during sepsis, in which the CIRP knock-out mice had reduced levels of neutrophil chemoattractants, MPO, and nitric oxide [10]. Thus, the role of CIRP on neutrophils in sepsis has been implicated but still remains to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In septic shock and lung stress induced in animal models by exposure to LPS and other TLR ligands, both oxidative stress and ER stress occur in the damaged lung and appear to be a feature of the pathological process 104, 105, 106. In sepsis/LPS‐induced lung injury, both ER stress and autophagy (which may be a response to ER stress) occur and the systemic factor cold‐induced RNA‐binding protein (CIRP), local inflammatory cytokines such as IL‐17 and neutrophil activation have been linked with the development of ER stress and activation of the UPR 104, 105, 106. Pulmonary arterial hypertension results in chronic hypoxia, inflammation, and consequently oxidative and ER stress, and induction of autophagy, in the respiratory mucosa 107.…”
Section: Oxidative and Er Stress In Acute Respiratory Conditionsmentioning
confidence: 99%